EFFECTS OF PRE-HARVEST METHYL JASMONATE TREATMENT ON POST-HARVEST FRUIT QUALITY OF JAPANESE PLUMS - Kucuker, Emine; Ozturk, Burhan (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Plum fruits constitute a good source of natural antioxidant substances. Particularly, plums contain large amounts of phenolic compounds and flavonoids having natural antioxidant activity which is effective in human diet. The aim of this study was to evaluate the effects of pre-harvest MeJA treatment on the fruit quality and bioactive compounds of three different Japanese plums under storage conditions.Materials and Methods: The effects of pre-harvest methyl jasmonate treatment (MeJA) on weight loss, color characteristics (L*, C* and h°), firmness, soluble solids content (SSC), titratable acidity (TA), total phenolics (TP) and total antioxidant activity (TAA) of ‘Black Beauty’, ‘Black Amber’ and ‘Fortune’ plum fruits during the cold storage (at 0±0.5 C and 90±5% RH) were investigated in this study. Results: MeJA did not have significant effects on the weight loss (%) of ‘Black Amber’ and ‘Fortune’ fruits, whereas it was effective in delaying the weight loss of ‘Black Beauty’ at the end of storage. The color characteristics of all plum cultivars were not significantly affected by MeJA at the end of storage. In all plum cultivars, the SSC increased, while TA significantly (P<0.05) decreased during storage. TP and TAA of ‘Black Amber’ and ‘Fortune’ fruits significantly increased during the cold storage. MeJA treatments increased fruit firmness, TP and TAA (according to FRAP) of ‘Fortune’ plums at the end of storage. Conclusion: The scientific results about the effects of pre-harvest MeJA treatments on the cold storage of Japanese plums may contribute significant helps to improve plum storage durations and quality characteristics.